Contribution to the Flora of Barak Valley: Conservation Status and Economic Potential of Herbaceous Plant Resources of Cachar District of Assam, India - Baruah, M. K.; Chakraborty, G.; Choudhury, M. Dutta (International Journal of Bio-resource and Stress Management, 2023)
The present paper focuses on the Contribution to the Flora of Barak Valley and their conservation status and Economic potential of herbaceous plant resources of Cachar district of Assam, India. Using traditional taxonomic techniques species have been collected from the study area during 2009-2012 and an attempt has been made to collect information on the economic uses of this species from the field through personal communications with the inhabitants of the remote villages and also collated from the earlier authentic works and available literature. In this study a total of 465 herbaceous species including cultivated ones under 116 families have been collected. Out of 465 species, about 242 economically important species have been recorded here which are used by the local people in different ways. Various anthropogenic activities and encroachment of forest leading to deforestation was observed frequently in many areas of the district and it is the main cause to destroy the habitat of herbaceous vegetation. Due to lack of accessibility, some of the floristically rich areas of the district remained totally unexplored. It is therefore important that conservation strategies be directed to protect the important forest areas of the district and special measures may be taken to explore the unexplored areas so that the rich herbaceous flora of the district could be documented and preserved.